Evaluation of Environmental Security of Ukraine during the Russian Invasion: State, Challenges, Prospects - SHVEDUN, Viktoriia; POSTUPNA, Оlenа; BULBA, Vоlodymyr; KUCHER, Lesia; ALIYEVA, Polina; IHNATIEV, Oleksandr (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023DO - 10.14505/jemt.14.3(67).18, 2023)
The authors propose to use the method of expert evaluations for studying the state of environmental security of Ukraine during the russian invasion of Ukraine as one of the most acceptable from the point of view of a combination of intuitive and rational approaches. In general, the amount of damage caused to the environment of Ukraine during the russian invasion due to various negative environmental events is 224982 million UAH. From the studies carried out, it is clear that the following components are the most problematic for the complex state policy in the field of environmental security of Ukraine: natural resource efficiency policy, environmental policy, licensing and standardization policy. Considering the situation in the field of environmental security of Ukraine during the russian invasion of Ukraine, it is recommended to supplement Ukraine Recovery Plan with the following National programs: (і) reforming public administration in the environmental industry; (іі) climate policy: preventing and adapting to climate change; (ііі) effective waste management; (і v ) conservation of natural ecosystems and biological diversity. Restoration and development of protected areas and facilities. The authors underline that intensification of the European integration policy will also contribute to the ecologization of the consciousness of Ukrainians. It is about a more economical attitude of the public towards natural resources, the responsibility of everyone for a clean environment for themselves and subsequent generations.